2004
DOI: 10.1111/j.1365-2672.2004.02219.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative survival of probiotic lactobacilli spray-dried in the presence of prebiotic substances

Abstract: Aims: Probiotic milk-based formulations were spray-dried with various combinations of prebiotic substances in an effort to generate synbiotic powder products. Methods and Results: To examine the effect of growth phase and inclusion of a prebiotic substance in the feed media on probiotic viability during spray-drying, Lactobacillus rhamnosus GG was spray-dried in lag, early log and stationary phases of growth in reconstituted skim milk (RSM) (20% w/v) or RSM (10% w/v), polydextrose (PD) (10% w/v) mixture at an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
242
1
18

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(277 citation statements)
references
References 41 publications
(118 reference statements)
16
242
1
18
Order By: Relevance
“…plantarum to desiccation. Optimal survival of spray drying was reported of Lactobacillus cultures in the stationary phase of growth (Corcoran et al 2004), which additionally proved to be more resistant to stress conditions (Kim et al 2001). Finally, the 4AE5-fold higher initial cell concentration could be made responsible for the better performance of Ent.…”
Section: Residual Moisture Content (%)mentioning
confidence: 97%
See 1 more Smart Citation
“…plantarum to desiccation. Optimal survival of spray drying was reported of Lactobacillus cultures in the stationary phase of growth (Corcoran et al 2004), which additionally proved to be more resistant to stress conditions (Kim et al 2001). Finally, the 4AE5-fold higher initial cell concentration could be made responsible for the better performance of Ent.…”
Section: Residual Moisture Content (%)mentioning
confidence: 97%
“…Another comparative study on this topic revealed contrary results, proving that susceptibility to certain drying methods is strongly dependent on the strain under evaluation (Zamora et al 2006). Focusing on fluidized bed drying thermal inactivation encountered during spray drying (Corcoran et al 2004) can be minimized by applying gentle process conditions, thus dehydration inactivation remains the main problem in convective drying (Linders et al 1997a). Furthermore the consequences of oxidation are very harmful especially to the membrane structure, thus oxygen-sensitive bacterial species suffer severe damage during convective air drying (Mille et al 2004).…”
Section: Residual Moisture Content (%)mentioning
confidence: 99%
“…En contraste, Pinto et al (2015) no observan efecto favorable en la viabilidad de bifidobacterias durante la encapsulación, ni durante el almacenamiento a 4 ºC y a -20 ºC. Por su parte Corcoran et al (2004) en sus estudios sobre el efecto comparativo de la supervivencia de lactobacilos encapsulados mediante secado por aspersión en presencia de sustancias prebióticas, verificaron que la inclusión del prebiótico inulina no incremento la viabilidad durante el almacenamiento de los encapsulados.…”
Section: Efecto De Los Agentes Prebióticos En La Liofilización Y Duraunclassified
“…The optimal growth phase for dehydration survival is the stationary phase. For instance, it has been reported that stationary phase cells of L. rhamnosus yielded the highest recovery rate after drying (31-50 % survival), but early log-phase cells exhibited only14% survival and lag phase cells showed the highest susceptibility, with only a 2 % cell survival under similar conditions of drying (Corcoran et al, 2004). Saarela et al (2004) reported that freeze drying and storage stability performance of B. animalis subsp.…”
Section: Important Parameters Affecting Microencapsulationmentioning
confidence: 99%